2011
DOI: 10.1167/11.10.9
|View full text |Cite
|
Sign up to set email alerts
|

High temporal resolution decoding of object position and category

Abstract: We effortlessly and seemingly instantaneously recognize thousands of objects, although we rarely--if ever--see the same image of an object twice. The retinal image of an object can vary by context, size, viewpoint, illumination, and location. The present study examined how the visual system abstracts object category across variations in retinal location. In three experiments, participants viewed images of objects presented to different retinal locations while brain activity was recorded using magnetoencephalog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
158
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(179 citation statements)
references
References 77 publications
19
158
2
Order By: Relevance
“…It is to be noted that some studies have used this method to assess cognitive processes, but they were not interested in extracting the detailed temporal dynamics of the processes (Chan, Halgren, Marinkovic, & Cash, 2011;Murphy et al, 2011). However, a few recent studies have begun to address this lack (Carlson, Hogendoorn, & Kanai, et al, 2011. For example, a recent study (Carlson, Hogendoorn, & Kanai, et al, 2011) showed that MEG responses could be used to categorize objects such as faces and cars.…”
Section: Applications Of Classification Methods To the Temporal Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…It is to be noted that some studies have used this method to assess cognitive processes, but they were not interested in extracting the detailed temporal dynamics of the processes (Chan, Halgren, Marinkovic, & Cash, 2011;Murphy et al, 2011). However, a few recent studies have begun to address this lack (Carlson, Hogendoorn, & Kanai, et al, 2011. For example, a recent study (Carlson, Hogendoorn, & Kanai, et al, 2011) showed that MEG responses could be used to categorize objects such as faces and cars.…”
Section: Applications Of Classification Methods To the Temporal Domainmentioning
confidence: 99%
“…However, a few recent studies have begun to address this lack (Carlson, Hogendoorn, & Kanai, et al, 2011. For example, a recent study (Carlson, Hogendoorn, & Kanai, et al, 2011) showed that MEG responses could be used to categorize objects such as faces and cars. Furthermore, the location of such objects could also be decoded, and the precision of this decoding depended on their cortical separation, arguing for representations in the early visual cortex, consistent with current results.…”
Section: Applications Of Classification Methods To the Temporal Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…We also conducted a discriminant cross-training (DCT) analysis [1]: A classifier is trained using patterns of neural activity at one time point t o and tested on all time points in the epoch, producing a matrix of decoding accuracy for each combination of training/testing time points (figure 4A). Note that the diagonals of these two matrices correspond to the decoding accuracy curves shown in figure 2C.…”
Section: Univariate Vs Multivariate Pattern Analysismentioning
confidence: 99%
“…Replicating previous reports, MEG sensor patterns could be used to accurately decode individual objects (Carlson et al, 2011;Carlson et al, 2013;van de Nieuwenhuijzen et al, 2013;Cichy et al, 2014;Isik et al, 2014;Clarke et al, 2015;Ritchie et al, 2015;Coggan et al, 2016;Kaiser et al, 2016a). Using representational similarity analysis, we then related MEG neural similarity to the objects' perceptual and categorical similarity.…”
Section: Discussionmentioning
confidence: 79%